Perkembangan Penelitian Green Sukuk: Analisis Bibliometrik dan Systematic Literature Review (SLR) - Adillah, Nurazizah; Handoko, Luqman Hakim; Firmansyah, Firmansyah (Fakultas Ekonomi, UIN Maliki Malang, 2024)
This study aims to analyze the publication trend of green sukuk. The data retrieved from Google Scholar using Publish or Perish. To analyze the data, bibliometric analysis using VOSviewer, and Systematic Literature Review were used in this study. The research findings indicate that the distribution of green sukuk studies can be grouped into 96 documents, with 22 documents (23%) being articles, 67 documents (70%) being journals, and 7 documents (7%) being proceedings. Based on language, the majority of the research is conducted in English (68%). The productivity of green sukuk research is evaluated in terms of the most productive journal, which is Environmental Economics (3), the most productive author, S Merlinda (4), the most productive country, Indonesia (69), and the most productive institution, the University of Indonesia. The most cited articles and authors are MA Naeem with 94 citations. The trend of research topics is analyzed based on the use of keywords with network visualization, and overlay visualization. Based on keywords, and SLR analysis, this study reveals 30 topics approximately need further investigation. Since this study focused on bibliometric, next study might deeply focused on SLR.